A Simplified Electroencephalogram Monitoring System in the Emergency Room. Issue 7 (July 2019) - Nozawa, Masahiro; Terashima, Hiroshi; Tsuji, Satoshi; Kubota, Masaya
Abstract : Objectives: The study aims to assess the clinical usefulness and related limitations of our simplified emergency electroencephalography (eEEG) as an assessment tool of lethal abnormal brain waves in the emergency room (ER). Methods: Electrodes were placed on 4 places: bilateral frontal poles and parietal regions. The derivations to judge consisted of only 2 bipolar leads on the left and right. Abnormal wave was defined as either persistent rhythmic waves or persistent high-amplitude slow waves (<2 Hz). The indications of eEEG were as follows: prolonged impairment of consciousness, suspected subclinical or subtle seizure, and requirement of evaluation of consciousness or seizure during administration of muscle relaxants for endotracheal intubation. Results: We performed eEEG for 86 patients between July 2013 and February 2014. The persistent rhythmic waves were observed in 7 (8.1%), whereas high-amplitude slow waves were observed in 10 (11.6%). Among 69 patients with normal eEEG, 2 were diagnosed with encephalopathy after hospitalization. The mean time taken to attach electrodes was 5.4 minutes. Conclusions: For the ER physician, the simple EEG, such as eEEG, is useful as a biological monitor because it enables quick assessment of lethal abnormal brain waves in the ER. The clinical usefulness and limitations of our eEEG method should be investigated further in a large population.